Metode Bernyanyi dalam Meningkatkan Penguasaan Kosa Kata Anak Usia Dini - Abu Hasan Agus R; Fathor Rozi; Itaqillah H.K (PALAPA, 2022)
This study aims to analyze and examine more deeply the implementation or application of the Learning Program through the singing method as an implementation method applied by RA Khairiyatul Amien, Ajung sub-district, Jember district, East Java. The singing method as an effort to succeed in children's learning has many benefits, including as a method of acquiring vocabulary and vocabulary for early childhood which tend to be very difficult to implicate. This study uses a descriptive qualitative approach with the type of case study research at RA Khairiyatul Amien. The data collection instrument in this study used observation and in-depth interviews as well as documentation to support the completeness of the data. The data analysis technique in this study was carried out with the stages of data collection, data reduction, data presentation, and conclusion of research results. In its implementation, the children voluntarily and cheerfully recorded the lyrics to the children's song under the direct guidance of the teacher. From this study, it was found that the singing method is very efficient and effective in continuous learning as well as mastering vocabulary in children because children have very high sensitivity to their hearing and sight so they tend to memorize and imitate easily. Of course, this success is coupled with consistency and continuous effort